An expeditious synthesis of 6, 7-dihydrodibenzo[b, j][4, 7] phenanthroline derivatives as fluorescent materials. Issue 42 (26th September 2022) - George, Kevin; Kannadasan, Sathananthan
Abstract : A rapid method has been developed for the synthesis of 13, 14-dimethyl-6, 7-dihydrodibenzo[ b, j ][4, 7]phenanthroline derivatives (3a–d ) through the Friedländer condensation of 2-aminoarylketone with 1, 4-cyclohexanedione under neat conditions using p -TSA. Abstract : A rapid and efficient method has been developed for the synthesis of 13, 14-dimethyl-6, 7-dihydrodibenzo[ b, j ][4, 7]phenanthroline derivatives (3a–d ) through the Friedländer condensation of 2-aminoarylketone with 1, 4-cyclohexanedione under solvent-free conditions using p -toluenesulphonic acid. The synthetic utility of compounds 3a, 3b, and 3c was demonstrated by synthesizing compounds 6a–k via Suzuki coupling, 8 by Buchwald–Hartwig amination, and 9a–b via NBS bromination. Significantly, the emission band corresponding to the π–π* electronic transition of compounds 3a, 6a, 6d, 6f, and 8 showed a redshift with increasing polarity of the solvents. Molar extinction coefficient ( ε ), Stoke's shift (Δ  ), and quantum yield ( Φ f ) were calculated for all these compounds.